Medieval Reliquaries and Their Role in Christian Processions - Mišković, Ana (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
This paper establishes a link between reliquaries and Christian processions, which can be traced back to the earliest times. The author first briefly presents the nature of processions that took place inside the sanctuary as well as outside of it, i.e. around its perimeter and across the city. Processions as transient events are evidenced by illustrative examples from the time, the most common and most famous being the Traditio legis motif: Christ flanked by the Apostles, lambs facing the cross in the centre, or a deer between kantharoi. Clear symmetry, axial harmony, and a parallel number of figures moving or facing Christ or his symbol in the centre prevail in all the examples. The same concept is present in smaller artefacts of the reliquary type, which were closely bound with or even integral to the nature of processions. Besides the figures that are harmoniously distributed across surfaces, they are characterized by the motif of arcades, prefiguring the (city) porches or the Heavenly Jerusalem. A notable number of medieval reliquaries preserved in Zadar have such a disposition of visual elements, which testifies to the concurrent processions. A source from the 14th century confirms that the Zadar reliquaries were carried in processions, and traces of later restoration or alteration of the original form have been observed in some of the examples. Sources from the early 18th century abound in data on processions held on feast days, when relics were brought out of their permanent repositories and carried around the sanctuary or the city.